Dry Matter and Essential Oil Yield Changes of Lavandula officinalis under Cowmanure and Vermicompost Application - Bohlool Abaszadeh; Parizad Mavandi; Mehdi Mirza (Journal of Medicinal Plants and By-products, 2016)
In order to study the effect of organic fertilizer on shoot yield and essential oil content of lavender, this experiment was conducted in the Research Institute of Forest and Rangelands, Karaj, Iran, in 2013-14. The treatment groups consisted of vermicompost (0, 5, 10 and 15 ton/ha) and cow manure (0, 10, 20 and 30 ton/ha). The experimental design was a factorial experiment based on randomized complete block design (RCBD) with three replications. The resultsshowed that cow manureapplication significantly affected big and smallcanopy diameter, canopy perimeter, lateral stems number and woody stem yield (P≤0.01). Moreover, manure significantly affected main stem diameter and leaf yield (P≤0.05). Results indicated that vermicompost application significantly affected big and smallcanopy diameter, annual stem number, leaf yield, annual stem yield, woody stem yield, total biological yield, essential oil yield (P≤ 0/01), and main stem (P≤ 0/05). According to the results, the interaction effect of treatments was significant for total shoot and leaf yield (P≤ 0/05). The highest sub stem number (24 n/p) was obtainedin 30 ton/ha manure treatment. While, the highest leaf yield (2206.4 kg/ha), annual stem yield (7133.2 kg/ha), annual branches yield (9933/6 kg/ha), total biological yield (1333.6 kg/ha) and essential oil yield (82.67 kg/ha) were determined at 15 ton/have vermicompost treatment. These fertilizers can improve tiller number and lateral stems growth but not affect essential oil percent and yield. It seems that they can increase it in drought stress condition because of improving soil moisture and fertility.